Distinct populations of identified glial cells in the developing rat spinal cord slice: ion channel properties and cell morphology - Chvátal, A; Pastor, A; Mauch, M; Syková, E; Kettenmann, H (The European journal of neuroscience, 1995)
Four types of glial cells could be distinguished in the grey matter of rat spinal cord slices at postnatal days 1-19 (P1-P19), based on their pattern of membrane currents as revealed by the whole cell patch clamp technique, and by their morphological and immunocytochemical features. The recorded cells were labelled with Lucifer Yellow, which allowed the subsequent identification of cells using cell-type-specific markers. Astrocytes were identified by positive staining for glial fibrillary acidic protein (GFAP). These were morphologically characterized by multiple, very fine and short processes and electrophysiologically by symmetrical, non-decaying K+ selective currents. Oligodendrocytes were identified by a typical oligodendrocyte-like morphology, lack of GFAP staining and positive labelling with a combination of O1 and O4 antibodies (markers of the oligodendrocyte lineage), and their membrane was dominated by symmetrical, passive, decaying K+ currents. The third population of glial cells was also characterized by positive staining for O1/O4 or only for O4 antigens, lack of GFAP staining and, in some cells, oligodendrocyte-like morphology. However, these cells could be distinguished by the presence of inwardly rectifying (KIR), delayed outwardly rectifying (KDR) and A-type K+ currents (KA), representing the most likely glial precursor cells of the oligodendrocyte lineage. The fourth population of glial cells had small somata and a widespread network of long processes with no apparent orientation preference. In one case, processes were positively labelled with GFAP, while 30% were characterized by faint, diffuse staining. These cells expressed a complex pattern of voltage-gated channels, namely Na+, KDR, KA and KIR channels. In contrast to neurons, the amplitude of Na+ currents was at least one order of magnitude smaller than the K+ currents, and none of these cells showed the ability to generate action potentials in the current clamp mode. Since none of these cells could be labelled by oligodendrocyte markers we assume that they were either astrocytes or glial precursor cells of the astrocyte lineage. The four cell types were found in all regions of the grey matter. When randomly accessing the glial cells, the probability of recording from the oligodendrocyte precursor cells and the glial cells with Na+ currents decreased during development. At P1-P3, 50% of the cells revealed the Na+ current, while at P13-P15 only 18% did. Concomitantly, the number of glial cells with astrocyte- and oligodendrocyte-like membrane currents increased from 19 and 12% to 41 and 35.5% respectively.(ABSTRACT TRUNCATED AT 400 WORDS)
Keywords: neuroglie; iontové kanály; Spinal Cord; Sodium Channels; Potassium Channels; Oligodendroglia; Neuroglia; akční potenciály; sodíkové kanály; Patch-Clamp Techniques; mícha; krysa rodu Rattus; zvířata; Action Potentials; Immunohistochemistry; draslíkové kanály; metoda terčíkového zámku; imunohistochemie; Astrocytes; Rats; Ion Channels; Animals; astrocyty; oligodendroglie